2015
DOI: 10.1186/s12989-015-0095-3
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous exposure to agglomerates of silica nanoparticles and allergen results in IgE-biased immune response and increased sensitivity to anaphylaxis in mice

Abstract: BackgroundThe skin is a key route of human exposure to nanomaterials, which typically occurs simultaneously with exposure to other chemical and environmental allergen. However, little is known about the hazards of nanomaterial exposure via the skin, particularly when accompanied by exposure to other substances.ResultsRepeated topical treatment of both ears and the shaved upper back of NC/Nga mice, which are models for human atopic dermatitis (AD), with a mixture of mite extract and silica nanoparticles induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 50 publications
3
19
0
Order By: Relevance
“…However, these nanoparticles decreased local skin inflammatory responses, such as cytokine induction, in this mouse model ( 38 ). Our group showed that topical skin painting with a mixture of SiO 2 nanoparticles and mite allergen suppressed allergen-specific IgG production without any changes in the IgE and Th1/Th2 immune responses ( 72 ). In addition, the suppression of IgG caused severe IgE-mediated hypersensitivity in an anaphylaxis model.…”
Section: Combined Exposure To Nanomaterials and Other Substancesmentioning
confidence: 99%
“…However, these nanoparticles decreased local skin inflammatory responses, such as cytokine induction, in this mouse model ( 38 ). Our group showed that topical skin painting with a mixture of SiO 2 nanoparticles and mite allergen suppressed allergen-specific IgG production without any changes in the IgE and Th1/Th2 immune responses ( 72 ). In addition, the suppression of IgG caused severe IgE-mediated hypersensitivity in an anaphylaxis model.…”
Section: Combined Exposure To Nanomaterials and Other Substancesmentioning
confidence: 99%
“…This choice of NP is based on the fact that the mean human adult intake of amorphous silica, which is used as a drug excipient or as a food additive and which is used for these purposes at concentrations ranging from 3 to 15 g/g of product (40), is estimated to be about 2 mg/kg of body weight/day (41). Although the nanosize nature of this material needs to be clarified (42), experiments suggest that SiO 2 NPs can enter intestinal epithelial cells and diffuse to the undermucosa or to the skin dermis (43)(44)(45)(46), where they may induce anaphylactic reactions (47,48). SiO 2 NPs are reported to induce cytotoxic, proinflammatory, and proimmune effects in murine DCs and skin Langerhans cells in vitro and in vivo (9,49,50).…”
mentioning
confidence: 99%
“…Furthermore, the authors have found that such response was inversely correlated with particle size. It has also been shown in a subsequent study by the same group that cutaneous exposure to agglomerates of silica nanoparticles (30 nm in diameter) and mite allergen resulted in a low IgG/IgE ratio and increased sensitivity to anaphylaxis (32). Another report has demonstrated that repeated topical exposure to ZnO nanoparticles (but not their bulk counterparts) in a BALB/c mouse model of AD, although suppressed local inflammation, resulted in aggravated response to the allergen (ovalbumin/staphylococcal enterotoxin B), which was manifested by elevated serum IgE levels suggesting a possible nanoparticle-specific role in priming Th2-type allergic responses (30).…”
Section: Evidence Of Enm-mediated Activation and Exacerbation Of Typementioning
confidence: 81%